Analysis of objective eye tracking data used for vehicle assessment - Jan Novotný (Acta Polytechnica CTU Proceedings, 2023)
This paper describes the application of eye tracking technology in the automotive industry in the context of vehicle assessment in customer clinics. The paper presents the mentioned technology, the applied experimental methodology and selected results. In particular, the hypotheses that were expressed during the research of the topic and during the preparation of the experiment are answered. In this way, the innovative technology of eye tracking can be used to reflect the "voice of the customer" in the vehicle design.